McDonald’s Customer’s Satisfaction Strategies during COVID-19 Pandemic in Malaysia - Edeh, Friday Ogbu; P V, Ranjith; Syafawani, Nurul; Kee, Daisy Mui Hung; Aina, Nurul; Syafikah, Nurul; Nurunnisa, Nurunnisa (AIBPM Publisher, 2021)
Generally, McDonald’s is recognized as one of the most successful brands worldwide. They are well-known throughout the world for their popular fast food, especially burgers. However, COVID-19 pandemic has impacted various economic sectors, including Food & Beverage. McDonald’s sales have also been impacted when COVID-19’s lockdown restricts the dine-in operation and limits the customer’s satisfaction due to the SOP. Thus, this research aims to identify and analyze the strategies implemented by McDonald’s to increase the customer’s satisfaction during Covid-19 pandemic. To find out the result of the research, a survey has been conducted and the data was collected from individuals with different age and income ranges in Malaysia. A total of 100 individuals have participated in this survey. Besides, in order to gain a better understanding of our study, secondary data for this study was gathered from a variety of websites, journals, and articles. The findings of this research indicate that McDonald's decision to increase the Food & Safety measure is by implementing various safety requirements. This is the most successful approach to improve customer’s satisfaction during COVID-19. They chose this strategy to demonstrate their commitment to preserve a healthy life.